2009
DOI: 10.1016/j.juro.2009.01.117
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of a Randomized, Double-Blind, Placebo Controlled Trial of Botulinum A Toxin for Refractory Overactive Bladder

Abstract: Purpose-We determined the effectiveness of cystoscopic administration of botulinum-A toxin compared to placebo for the treatment of urinary incontinence in subjects with idiopathic overactive bladder.Materials and Methods-Subjects were recruited from the Division of Urogynecology at the University of Rochester. Inclusion criteria were overactive bladder refractory to anticholinergic medications, multiple daily incontinence episodes and a 24hour pad weight of 100 gm or greater. Subjects with low leak point pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
85
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 20 publications
10
85
1
4
Order By: Relevance
“…Worth of noting, incomplete voiding symptoms were unrelated to the BoNT/A dosage used. Also patients with multiple sclerosis treated with 100 Units and patients with idiopathic overactive bladder treated with 200 and 300 units of BoNT/A showed an increase in post-void residual volume (Flynn et al, 2009;Mehnert et al, 2010;Sahai et al, 2009). Our results on post-void residual volume are in contrast with those reported by Kulaksizoglu and Parman (Kulaksizoglu & Parman, 2010) who treated parkinsonian patients with Dysport 500 Units.…”
Section: Discussioncontrasting
confidence: 88%
“…Worth of noting, incomplete voiding symptoms were unrelated to the BoNT/A dosage used. Also patients with multiple sclerosis treated with 100 Units and patients with idiopathic overactive bladder treated with 200 and 300 units of BoNT/A showed an increase in post-void residual volume (Flynn et al, 2009;Mehnert et al, 2010;Sahai et al, 2009). Our results on post-void residual volume are in contrast with those reported by Kulaksizoglu and Parman (Kulaksizoglu & Parman, 2010) who treated parkinsonian patients with Dysport 500 Units.…”
Section: Discussioncontrasting
confidence: 88%
“…Seven trials compared botulinum toxin-A with placebo [6,7,8,9,10,11,14,16,18,19,20]. They included 782 patients; 23 patients were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of patients with >75% improvement in urgency and urge urinary incontinence episodes at month 3 was greater in all botulinum toxin-A groups in Denys et al's study (p = 0.03) [11]. Compared with baseline at 6 weeks (p = 0.02), in Flynn et al's study [19], nocturia was reduced in the whole botulinum toxin-A group, however, there was no difference between botulinum toxin-A and placebo in nocturia reduction (p = 0.91). According to the measure of the Patient Global Impression of Improvement scale, Brubaker et al [18] found that 60% of patients receiving 200 U botulinum toxin-A had a clinical response at month 2.…”
Section: Resultsmentioning
confidence: 99%
“…Data have been given about changes in QoL due to treatment and about PVR and UTIs at week 12, which were less than 50 ml and 15.5-20.4%, respectively. Also, in other published studies, local anesthesia has been used to treat patients with idiopathic OAB, in an outpatient setting (11)(12)(13)(14)(15). Nevertheless, all these studies did not mention patients' satisfaction with treatment, but they often report on satisfaction about changes in urinary symptoms and QoL.…”
Section: Discussionmentioning
confidence: 99%